Kajian Studi Literatur: Memahami Keingintahuan Siswa Dalam Pembelajaran - Laesti Nurishlah; Siti Mariam; Mochammad Ramdan Samadi (STAI Al-Mas'udiyah, 2023)
This study aims to understand how students feel about the learning process in their classrooms. In this research, 20 students were interviewed to explore the variability in their level of curiosity towards learning materials. The results show that students' attitudes towards learning tend to vary; sometimes they feel very interested in learning, while at other times, they do not feel interested at all. Factors influencing students' feelings towards learning include how interesting they find the topic, their confidence in their academic abilities, their perception of the importance of the learning, and the support they receive from their teachers in sparking their interest in learning. The research highlights that students' disinterest in learning may be caused by several factors, such as the lack of interest in the topics taught, student fatigue, or a lack of understanding of the relevance of the material. Therefore, the study suggests that teachers need to create more engaging learning experiences and demonstrate the usefulness of the material in order to enhance students' interest in learning.